Wild Boar Events and the Veterinarization of Multispecies Coexistence - Broz, Ludek; Arregui, Aníbal Garcia; O'Mahony, Kieran (Frontiers in Conservation Science, 2021)
By considering the emergence and threat of African Swine Fever (ASF) in Europe, this paper demonstrates the growing role of veterinary rationales in reframing contemporary human-wild boar coexistence. Through comparative ethnographies of human-wild boar relations in the Czech Republic, Spain and England, it shows that coexistence is not a predictable and steady process but is also demarked by points of radical change in form, course and atmosphere. Such moments, or wild boar events, can lead to the (re-)formation or magnified influence of certain discourses, practices and power relations in determining strategies of bio-governance. Specifically, this paper highlights how the spread of ASF in Europe has accelerated an already ongoing process of veterinarization, understood as the growing prominence of veterinary sciences in the mediation and reorganization of contemporary socioecologies. This example highlights how veterinary logics increasingly influence localized human-wildlife relations and, through analogous practices of biosecurity and control, also connect different places and geographic contexts.